Evaluation of leishmanicidal effect of Euphorbia petiolata extract by in vivo anti-leishmanial assay using promastigotes of Leishmania major - Reza Kazemi Oskuee; Mahmoud Reza Jafari; Mahdi Moghaddasi; mahdi rivandi; fahimeh Afzal Javan; mohammad mohajeri; Mohammad Ramezani (Mashhad University of Medical Sciences, 2018)
Objective: The extract of different species of Euphorbia has been successfully used as a remedy for treatment of cutaneous leishmaniasis. The aim of this study was to assess the in vitro leishmanicidal effect of Euphorbia petiolata (E. petiolata) extract. Materials and Methods: Ethanolic percolated and methanolic Soxhlet extract of E. petiolata on promastigotes of L. major at different concentrations of extracts, one positive control group and one negative control group as well as 1 solvent control were prepared and placed in 24-well plates that contained 40,000 parasites/well. Afterwards, plates were incubated at 25 ˚C for six days and number of parasites in each well were determined on days 2, 4 and 6 of the experiment. Results: Both percolated and Soxhlet extracts in methanol and DMSO solvents had significant effects (equal to that of amphotericin B) on promastigote form of parasite at the concentration of 1 mg/ml. At lower concentrations, the extracts of E. petiolata had favorable leishmanicidal activity and killed L. major promastigotes dose-dependently. Conclusion: Our results support the possibility of E. petiolata extracts application as an anti-leishmanial agent with similar effects to amphotericin B.